2017
DOI: 10.1039/c7sm01771e
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic streamers in a microfluidic system

Abstract: In this work, we report the phenomenon of formation of particle aggregates in the form of thin slender strings when a polyacrylamide (PAM) solution, laden with polystyrene (PS) beads is introduced into a microfluidic device containing an array of micropillars. PAM and a dilute solution of PS beads are introduced into the microfluidic channel through two separate inlets and localized particle aggregation is found to occur under certain flow regimes. The particle aggregates initially have a string-like morpholog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…Debnath et al . 35 recently demonstrated that particle laden polymeric flows can also lead to morphologically similar structures as bacterial streamers leading to the generalization of the phenomenon to other colloidal systems. When a mixture like particle laden polymer (PAM(0.2%):PS(0.2%) = 1:4) is filtered through our MMM system, a filamentous compliant structure was formed at downstream of the pillars.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Debnath et al . 35 recently demonstrated that particle laden polymeric flows can also lead to morphologically similar structures as bacterial streamers leading to the generalization of the phenomenon to other colloidal systems. When a mixture like particle laden polymer (PAM(0.2%):PS(0.2%) = 1:4) is filtered through our MMM system, a filamentous compliant structure was formed at downstream of the pillars.…”
Section: Resultsmentioning
confidence: 99%
“…Pore-blockage (inside the pores) is seen when PAM only solution is flown through the MMM device. The PAM molecules have a radius of gyration, R g = 191.9 nm 35 , and their entanglement can completely block the pores during the course of filtration (Fig. 2(b)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GPV yields flow velocities using sub-resolution tracers similar to micro Particle Image Velocimetry 34 ( ). The tracer particles are added in low concentration to the sample fluid in order to avoid aggregations 35 . The moving particles generate an interference pattern which is advected by the flow (" Methods " section).…”
Section: Resultsmentioning
confidence: 99%
“…All these studies discussed particle migration in periodic arrays of pillars in Newtonian fluids and there are even fewer studies that study particle migration with non-Newtonian fluids. [16][17][18] Jacob et al 17 investigated the particle dispersion of 2 mm particles in a Newtonian and shear-thinning elastic fluid (HPAM) and they presented an analysis of the influence of elastic instabilities. However, due to the presence of both elasticity and shearthinning properties in HPAM, the effect of each property could not be studied separately.…”
Section: Introductionmentioning
confidence: 99%